The effect of iron versus iron plus zinc supplementation in children with malaria - Bugis Mardina Lubis; Danny Dasraf; Nelly Rosdiana; Bidasari Lubis; Munar Lubis; Syahril Pasaribu; Chairuddin P Lubis (Indonesian Pediatric Society Publishing House, 2016)
Introduction Little is known about the potential interaction of iron and zinc given to increase hemoglobin and serum ferritin in chil- dren with malaria. Objective To study the effect of iron compared with a combination of iron and zinc supplementation on children with falciparum malaria. Method Children with positive Plasmodium falciparum (n=86) were randomly assigned to a daily supplementation of 6 mg iron/kg per day plus placebo or plus 10 mg zinc per day for 30 days. All children were treated with the same regimen for the treatment of P. falciparum. Venous blood samples were collected at the start and end of the study. After 30 days of supplementation, the baseline and follow-up blood samples were analyzed. Results The increase of hemoglobin concentration in the iron plus placebo group was 0.58 g/dl, while in the iron plus zinc group was 0.09 g/dl (P<0.05). Serum ferritin concentration was high in both groups before trial, yet there was no significant difference after iron supplementation. Conclusions Iron supplementation showed significant increase in hemoglobin concentration in children with positive P. falciparum treated with the same regimen of treatment. Supplementation of iron alone as well as iron plus zinc had been proven ineffective to iincrease serum ferritin in children with malaria.